2016
DOI: 10.3390/cells5040038
|View full text |Cite
|
Sign up to set email alerts
|

Segmental Aging Underlies the Development of a Parkinson Phenotype in the AS/AGU Rat

Abstract: There is a paucity of information on the molecular biology of aging processes in the brain. We have used biomarkers of aging (SA β-Gal, p16Ink4a, Sirt5, Sirt6, and Sirt7) to demonstrate the presence of an accelerated aging phenotype across different brain regions in the AS/AGU rat, a spontaneous Parkinsonian mutant of PKCγ derived from a parental AS strain. P16INK4a expression was significantly higher in AS/AGU animals compared to age-matched AS controls (p < 0.001) and displayed segmental expression across va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 63 publications
1
5
0
Order By: Relevance
“…In this study actually demonstrated for Parkinson disease, which however has been shown in rat models to resemble accelerated brain aging(Khojah et al 2016). …”
supporting
confidence: 59%
“…In this study actually demonstrated for Parkinson disease, which however has been shown in rat models to resemble accelerated brain aging(Khojah et al 2016). …”
supporting
confidence: 59%
“…There are nine PKC genes in mammals, which are subdivided into three subfamilies: conventional PKC α, β, and γ, neo-PKC δ, ε, θ, η, and atypical PKC ε and ι ( Steinberg, 2008 ). The Parkinsonian phenotype and disruption to dopamine signaling in the basal ganglia are found in AS/AGU (Albino Swiss/Anatomy Glasgow University) rats ( Khojah et al, 2016 ). Knockout of PKC γ in animals, exhibits PD symptoms, such as loss of nigrostriatal dopaminergic neurons and movement disorder ( Shirafuji et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Chiral molecules are molecules with two mirror-image forms, and the molecule chirality plays an important role in living systems. The chiral components in living systems usually exist in only one mirror-image form. For example, nucleotides and sugars are in the d -form, while phospholipids and amino acids are in the l -form. , These chiral components are of great significance to various living processes (such as cell metabolism and cell fate). , Chiral drugs can cause different or even opposite effects, such as l -Dopa (a drug used to treat Parkinson’s disease) and ibuprofen (anti-inflammatory and analgesic) …”
Section: Introductionmentioning
confidence: 99%
“…6,7 Chiral drugs can cause different or even opposite effects, such as L-Dopa (a drug used to treat Parkinson's disease) and ibuprofen (anti-inflammatory and analgesic). 8 Currently, chiral research has expanded from organic molecules to inorganic nanoparticles (NPs). 9−12 Due to their specific photochemical properties, chiral nanoparticles have been applied in many fields, such as biological behavior regulation, chiral sensing, enantiomeric separation, chiral catalysis, etc.…”
Section: ■ Introductionmentioning
confidence: 99%